2007
DOI: 10.1097/01.ta.0000236019.00650.00
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment With Pro- and Synbiotics Reduces Peritonitis-Induced Acute Lung Injury in Rats

Abstract: Three weeks of preoperative enteral administration of a synbiotic composition reduced peritonitis-induced acute lung injury in rats in a CLP model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…Tok and et al showed that symbiotic treatment reduced pulmonary tissue injury in intra-abdominal sepsis [31]. In the present study, it was observed that probiotic treatment reduced both pancreatic and pulmonary tissue damage in ANP.…”
Section: Discussionmentioning
confidence: 53%
“…Tok and et al showed that symbiotic treatment reduced pulmonary tissue injury in intra-abdominal sepsis [31]. In the present study, it was observed that probiotic treatment reduced both pancreatic and pulmonary tissue damage in ANP.…”
Section: Discussionmentioning
confidence: 53%
“…In this study the serum endotoxin level in alcohol-treated rats was 190.0 ± 140.7 pg ml -1 , which was over 19-fold higher than in the LAB-fed group (10.5 ± 9.3 pg ml -1 , P = 0.01). In our previous study [16,17], and also in various other studies [18][19][20], LAB was shown to be able to effectively preserve gut barrier integrity and prevent endotoxemia through cellular immunity, to stimulate production of suppressive cytokines (TGF-b, IL-10), to suppress CD4 ? T-cells and Th2 activity, and to decrease specific IgE and IgG 1 .…”
Section: Discussionmentioning
confidence: 98%
“…(74) Further studies in animal models and humans, using Lc. mesenteroides strains alone should be done in order to confirm and understand the behavior of this microorganism in the host GIT.…”
Section: Metabolic Activitymentioning
confidence: 99%
“…(73) Further, a reduction of acute induced-peritonitis lung injury in rats was shown with preoperative enteral administration of symbiotic composition (10 9 CFU/g of each A c c e p t e d M a n u s c r i p t 16 edema (wet-to-dry lung weight ratio) was significantly reduced in the symbiotic-treated group (4.92 ± 0.13 vs. 5.07 ± 0.08 and 5.39 ± 0.10, respectively). (74) Further studies in animal models and humans, using Lc. mesenteroides strains alone should be done in order to confirm and understand the behavior of this microorganism in the host GIT.…”
Section: Metabolic Activitymentioning
confidence: 99%